Virus Newcastle (Baka/Strain Af-2240) Ekspresi Gen Hn Ke dalam Sel Kanser Colon Apoptotik Manusia (Ht-29) - Khodai, Samira (2009)
Newcastle disease virus (NDV) is the causative agent of the Newcastle disease (ND). The virus has been used as vaccines in veterinary medicine to protect poultry against pathogenic NDV strains which causes respiratory disease but NDV in humans has interesting anti-neoplastic and immune stimulating properties. NDV can be oncolytic and activate host immune cells to produce cytokines and to become cytotoxic against tumour cells via unknown mechanism. The recombinant haemagglutinin-neuraminidase (HN) protein was obtained from Malaysian viserotropic-velogenic NDV strain AF2240 through reverse transcription-polymerase chain reaction (RT-PCR) and cloned into the mammalian expression vector pEGFP-N2. The constructed recombinant plasmid which was named pEGFP-N2/HN was used to transform into Escherichia coli Top 10 for amplification. The extracted plasmid from E. coli Top 10 was then used for transfection and apoptosis studies. The constructed plasmid, pEGFP-N2/HN, was transfected into HT-29 (human colon cancer) cell line and HeLa (human cervical cancer) cell line for protein expression and apoptosis studies, the 3T3 (normal mouse fibroblast) cell line was selected as control cell lines. At 72 h post-transfection, protein expression of constructed pEGFP-N2/HN was analysed using SDS-PAGE, Western Blot and fluorescence microscope. It was shown that the recombinant HN gene was expressed in HT-29 cell as well as HeLa cells and 3T3 cells. The cytotoxic effects of NDV strain AF2240 was determined by MTT assay. Results from MTT assay showed that 50% inhibitory concentration (IC50) value in HT-29 cells obtained by 384 HA titer unit after 24 h while this amount decrease to 80 HA titer unit in HeLa cells during the same period. However after 48 h treatment IC50 in HT-29 cells obtained by 380 HA titer unit and in HeLa cells this amount decreased to 64 HA titer unit. At 72 h treatment IC50 of HT-29 cells was obtained by 300 HA titer unit, in HeLa cells this amount was only 4 HA titer unit. In 3T3 cells no inhibition effect was observed after infection with NDV strain AF2240. The apoptosis effects of NDV strain AF2240 infection and pEGFP-N2/HN expression on HT-29, HeLa and 3T3 cell were analysed by Flow cytometry in which Propidium Iodide was used for cell staining, the untreated cells were considered as control. Infection studies were carried out with NDV strain AF2240 at its IC50 HA titer unit for 24, 48 and 72 h. Transfection studies were performed with 4 μg of constructed plasmid, pEGFP-N2/HN, for 72 h. Flow cytometry results from pEGFP-N2/HN transfection studies showed the involvement of HN gene expression of NDV strain AF2240 in inducing apoptosis in tumour cells but not normal cells. Flow cytometry result from transfection studies showed that the apoptosis induction of pEGFP-N2/HN transfection in HeLa cells was higher than apoptosis induction in HT-29 cells. Early apoptosis effect of NDV strain AF2240 infection and pEGFP-N2/HN transfection on HT-29, HeLa and 3T3 cell were analysed by Flow cytometry in which Annexin V staining was used, in all experiments untreated cells were considered as control. The Flow cytometry results showed that NDV strain AF2240 infection was able to trigger early apoptosis in tumour cell line after 12 h while transfection of tumour cells with pEGFP-N2/HN induced early apoptosis after 24 h, no early apoptosis induction has been observed in normal cells. In conclusions the recombinant HN gene of NDV strain AF2240 expressed in human colon cancer cells (HT-29) and human cervical cancer cells (HeLa) as well as mouse normal fibroblast cells (3T3). The expressed recombinant HN protein of NDV strain AF2240 induced apoptosis in human tumor cells (HT-29 and HeLa) without any cytotoxic effects on normal fibroblast cells.